(untitled) (Práxis Educativa, 2024)
This paper presents results of a research whose central objective was to investigate the pedagogical praxis of teachers who teach Mathematics in Multifunctional Resource Rooms in the early grades of Elementary School. The research, qualitative and exploratory in nature, to collect data, used a questionnaire sent remotely to teachers who work in these classrooms. To process the data, an assessment inspired by the Discursive Textual Analysis was chosen. The study proved to be relevant, considering that it addressed emerging issues of the school universe and that concern the inclusion and teaching of Mathematics subject in the Multifunctional Resource Rooms of this level, in addition to inventorying information on public policies for the area and perform theoretical reflections on related themes, aiming to support improvements in the scope of practices undertaken in these peculiar Basic Education environment, as well as thinking about directions for more assertive and punctual continued training for teachers. Keywords: Specialized Educational Service. Multifunctional Resource Room. Inclusive teaching.